And here my troubles began - Spiegelman, Art.; Fili, Louise; Spiegelman, Art; Pantheon Books (New York : Pantheon Books, 1991)
A memoir of Vladek Spiegleman, a Jewish survivor of Hitler's Europe, and about his son, a cartoonist who tries to come to terms with his father, his story, and history. Cartoon format portrays Jews as mice, Nazis as cats. Using a unique comic-strip-as-graphic-art format, the story of Vladek Spiegelman's passage through the Nazi Holocaust is told in his own words. Acclaimed as a "quiet triumph" and a "brutally moving work of art," the first volume of Art Spiegelman's Maus introduced readers to Vladek Spiegelman, a Jewish survivor of Hitler's Europe, and his son, a cartoonist trying to come to terms with his father, his father's terrifying story, and History itself. Its form, the cartoon (the Nazis are cats, the Jews mice), succeeds perfectly in shocking us out of any lingering sense of familiarity with the events described, approaching, as it does, the unspeakable through the diminutive. As the New York Times Book Review commented," [it is] a remarkable feat of documentary detail and novelistic vividness ... an unfolding literary event." This long-awaited sequel, subtitled And Here My Troubles Began, moves us from the barracks of Auschwitz to the bungalows of the Catskills. Genuinely tragic and comic by turns, it attains a complexity of theme and a precision of thought new to comics and rare in any medium. Maus ties together two powerful stories: Vladek's harrowing tale of survival against all odds, delineating the paradox of daily life in the death camps, and the author's account of his tortured relationship with his aging father. Vladek's troubled remarriage, minor arguments between father and son, and life's everyday disappointments are all set against a backdrop of history too large to pacify. At every level this is the ultimate survivor's tale -- and that too of the children who somehow survive even the survivors.
"Manufactured in the United States of America ; Book design: Art Spiegelman and Louise Fili"--Title page verso.
105499
Keywords: Spiegelman, Vladek -- Comic books, strips, etc; Spiegelman, Art -- Comic books, strips, etc; Auschwitz (Concentration camp) -- Comic books, strips, etc; 1939-1945; Holocaust, Jewish (1939-1945) -- Poland -- Biography -- Comic books, strips, etc; Holocaust survivors -- Poland -- Biography -- Comic books, strips, etc; Children of Holocaust survivors -- United States -- Biography -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Mice -- Comic books, strips, etc; Fathers and sons -- Comic books, strips, etc; Nazis -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; War -- Comic books, strips, etc; Death -- Comic books, strips, etc; Prisoners -- Comic books, strips, etc; Graphic novels; Comic books, strips, etc